Estimating the tensile strength of super hard brittle materials using truncated spheroidal specimens. (May 2015) - Serati, Mehdi; Alehossein, Habib; Williams, David J.
Abstract: New approaches need to be introduced to measure the tensile capacity of super hard materials since the standard methods are not effective. To pursue this objective, a series of laboratory tests were constructed to replicate the fracture mechanism of diamond-based materials. Experiments indicate that under a certain compressive test condition, stresses normal to the axisymmetric line in truncated spheroidal specimens (bullet-shaped specimens) are in tension contributing to the tensile fracture of the material. From experimental and numerical studies, it is concluded that semi-prolate spheroidal specimens can be used to determine precisely the tensile strength of brittle stiff diamond-like composites. Abstract : Graphical abstract: Abstract : Highlights: A series of laboratory tests with truncated spheroidal specimens of thermally stable diamond specimens, glass ceramic and graphite were carried out to find an alternative solution for the estimation of the tensile strength of super hard brittle materials. Experimental measurements indicated that under a certain compressive test condition, stresses normal to the axisymmetric line in truncated spheroidal specimens are in most places in tension resulting in a tensile fracture of the samples. Results showed that semi-prolate spheroidal specimens can be conveniently adopted, instead of standard specimen profiles, to determine the tension bearing capacity of a highly brittle and stiff material.